2020
DOI: 10.3389/fphys.2020.574124
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Tendinous, Myotendinous and Myofascial Injuries by L-BIA in Professional Football Players

Abstract: Purpose: To differentiate by localized bioimpedance (L-BIA) measurements 24 h after injury, between tendinous, myotendinous junction (MTJ), and myofascial junction (MFJ) injuries, previously diagnosed by MRI exam. To evaluate by L-BIA, the severity of MTJ injuries graded from 1 to 3, and to determine the relationship between days to return to play (RTP) and L-BIA measurements. Methods: 3T MRI and tetra polar L-BIA was used to analyzed 37 muscle injuries 24 h after injury in 32 male professional football player… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…In the measurement of segmental bioimpedance, the two injector electrodes are located and fixed in the metacarpophalangeal and metatarsophalangeal joints, while the sensing electrodes are usually placed at the end of the superior and inferior limbs [ 111 , 112 , 113 , 114 , 115 , 116 ]. On the contrary, in L-BIA measurements, the four electrodes are applied on the body region of interest, such as specific muscles [ 45 , 58 , 93 , 117 , 118 ].…”
Section: Bioelectric Impedance Analysis (Bia) In Athletesmentioning
confidence: 99%
“…In the measurement of segmental bioimpedance, the two injector electrodes are located and fixed in the metacarpophalangeal and metatarsophalangeal joints, while the sensing electrodes are usually placed at the end of the superior and inferior limbs [ 111 , 112 , 113 , 114 , 115 , 116 ]. On the contrary, in L-BIA measurements, the four electrodes are applied on the body region of interest, such as specific muscles [ 45 , 58 , 93 , 117 , 118 ].…”
Section: Bioelectric Impedance Analysis (Bia) In Athletesmentioning
confidence: 99%
“…This indicates that EIM is sensitive to the muscle swelling induced by exercise (Shiffman et al, 2003;Freeborn and Fu, 2019). On the other hand, changes in Xc values were similar to those observed in severe injuries (Nescolarde et al, 2013(Nescolarde et al, , 2015(Nescolarde et al, , 2017(Nescolarde et al, , 2020. Information on the PhA values and how 1RM was assessed was not provided.…”
Section: Medium-term Adaptationsmentioning
confidence: 96%
“…A total number of 607 subjects were involved in the studies included in the review, in addition to the unspecified number of participants in the study of Nescolarde et al (2015), who only indicated 21 muscle injuries. Seven studies were carried out with elite soccer athletes, of which two involved non-injured subjects (Mascherini et al, 2015(Mascherini et al, , 2017 and five involved subjects with skeletal muscle injury (Nescolarde et al, 2013(Nescolarde et al, , 2015(Nescolarde et al, , 2017(Nescolarde et al, , 2020Francavilla et al, 2015). Despite all the studies including healthy subjects, one of them compared their data with those of a preliminary study in patients with neuromuscular disease in one section of the article (Shiffman et al, 2003), while another included healthy subjects alongside data from healthy control subjects of a previous study focused on neuromuscular disorders, excluding those with disorders (Aaron et al, 2006).…”
Section: Participants and Characteristics Of The Studiesmentioning
confidence: 99%
See 2 more Smart Citations